2021
DOI: 10.1038/s41419-021-04367-3
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab promotes RSL3-induced ferroptosis by suppressing the Nrf2/HO-1 signalling pathway in KRAS mutant colorectal cancer

Abstract: Cetuximab is approved for the treatment of metastatic colorectal cancer (mCRC) with RAS wild-type. Nevertheless, the prognosis remains poor and the effectiveness of cetuximab is limited in KRAS mutant mCRC. Recently, emerging evidence has shown that ferroptosis, a newly discovered form of nonapoptotic cell death, is closely related to KRAS mutant cells. Here, we further investigated whether cetuximab-mediated regulation of p38/Nrf2/HO-1 promotes RSL3-induced ferroptosis and plays a pivotal role in overcoming d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(98 citation statements)
references
References 48 publications
2
74
0
Order By: Relevance
“…25 For example, cetuximab promoted RSL3-induced ferroptosis by regulating the Nrf2/ HO-1 signaling pathway in KRAS mutant colorectal cancer. 26 Metallothionein-1G has been reported as a negative regulator of ferroptosis, leading to sorafenib resistance in hepatocellular carcinoma. 27 And miR-522 secreted by cancer-associated fibroblasts promoted acquired chemo-resistance in gastric cancer via blocking lipid-ROS accumulation and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 For example, cetuximab promoted RSL3-induced ferroptosis by regulating the Nrf2/ HO-1 signaling pathway in KRAS mutant colorectal cancer. 26 Metallothionein-1G has been reported as a negative regulator of ferroptosis, leading to sorafenib resistance in hepatocellular carcinoma. 27 And miR-522 secreted by cancer-associated fibroblasts promoted acquired chemo-resistance in gastric cancer via blocking lipid-ROS accumulation and ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis, first coined by Dr. Brent R Stockwell in 2012, 24 is a new form of programmed cell death characterized by the accumulation of iron‐dependent lethal lipid peroxides, linking to cancer initiation, development, metastasis, and especially drug effectiveness 25 . For example, cetuximab promoted RSL3‐induced ferroptosis by regulating the Nrf2/HO‐1 signaling pathway in KRAS mutant colorectal cancer 26 . Metallothionein‐1G has been reported as a negative regulator of ferroptosis, leading to sorafenib resistance in hepatocellular carcinoma 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The Keap1/Nrf2/HO-1 signalling pathway is recognised as an important antioxidant system that protects cancer cells from ferroptosis ( Lippmann et al, 2020 ). In KRAS -mutant colorectal cancer cells, inhibition of the Nrf2/HO-1 axis contributed to the promotion of ferroptosis induced by RSL3, a GPX4 inhibitor ( Yang et al, 2021 ). Here, we revealed that nobiletin could inhibit the Keap1/Nrf2/HO-1 axis in SK-MEL-28 cells, which might be the potential mechanism of nobiletin-induced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased HRAS expression levels promote gastric carcinoma cell aggressiveness [ 34 ]. Resent research has reported that the blockade of Nrf2/HO-1 signaling promotes RSL3-induced ferroptosis in KRAS mutant colorectal cancer [ 35 ]. However, it was reported that KRAS mutations were rarely found in CSCC but were frequently observed in cervical adenocarcinomas, indicating that KRAS mutations in CSCC were uncommon [ 36 ].…”
Section: Discussionmentioning
confidence: 99%